Reading comprehension in english language and its influence in the meaningful learning - Isabel Grimanesa Olín Zegarra (2019)
The main objective of the present research is to determine the relationship of reading comprehension in English with meaningful learning, among students from the third semester of the specialty of Initial Education from the Institute of Higher Education Pedagogical Public Arequipa and to present a proposal to enhance and to strengthen their weaknesses. Through this research it is explained that reading comprehension is a more complex process in a second language because it is not just about identifying words and meanings, in English language teaching, this skill is very important because it implies understanding and interpreting a with what the reader knows. Likewise, it is about explaining that meaningful learning is the process where information could be obtained, selected, organized and combined with knowledge or previous experiences.This research is of application level and the research type corresponds to a descriptive-correlational investigation with a quantitative approach, since the study aims to establish the relationship between the independent variable and the dependent variable, The results obtained by the statistical analysis indicate that there is a strong correlation between the reading comprehension variable and the significant learning variable, showing a Pearson correlation coefficient of 0.766, that is, higher results in reading comprehension correspond to the greater results in meaningful learning. or vice versa.